Descompuneti in factori:(y-3)+(y+1)³
Răspunsuri la întrebare
Răspuns de
0
= ( y -3 + y +1) ·[ ( y -3)² - ( y - 3)·( y +1) + ( y +1)² ] =
=(2y - 2 ) ·( y² - 6y + 9 - y² + 3y - y + 3 + y² + 2y +1)
= 2· ( y - 1)· ( y² -2y +13)
=(2y - 2 ) ·( y² - 6y + 9 - y² + 3y - y + 3 + y² + 2y +1)
= 2· ( y - 1)· ( y² -2y +13)
Alte întrebări interesante
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă